Activation of CO2 assimilation during photosynthetic induction is slower in C4 than in C3 photosynthesis in three phylogenetically controlled experiments - Arce Cubas, Lucía; Vath, Richard L.; Bernardo, Emmanuel L.; Sales, Cristina Rodrigues Gabriel; Burnett, Angela C.; Kromdijk, Johannes (Frontiers in Plant Science, 2023)
Introduction Despite their importance for the global carbon cycle and crop production, species with C4 photosynthesis are still somewhat understudied relative to C3 species. Although the benefits of the C4 carbon concentrating mechanism are readily observable under optimal steady state conditions, it is less clear how the presence of C4 affects activation of CO2 assimilation during photosynthetic induction. Methods In this study we aimed to characterise differences between C4 and C3 photosynthetic induction responses by analysing steady state photosynthesis and photosynthetic induction in three phylogenetically linked pairs of C3 and C4 species from Alloteropsis, Flaveria, and Cleome genera. Experiments were conducted both at 21% and 2% O2 to evaluate the role of photorespiration during photosynthetic induction. Results Our results confirm C4 species have slower activation of CO2 assimilation during photosynthetic induction than C3 species, but the apparent mechanism behind these differences varied between genera. Incomplete suppression of photorespiration was found to impact photosynthetic induction significantly in C4Flaveria bidentis, whereas in the Cleome and Alloteropsis C4 species, delayed activation of the C3 cycle appeared to limit induction and a potentially supporting role for photorespiration was also identified. Discussion The sheer variation in photosynthetic induction responses observed in our limited sample of species highlights the importance of controlling for evolutionary distance when comparing C3 and C4 photosynthetic pathways.